Upaya Meningkatkan Aktivitas dan Hasil Belajar IPA Fisika Pada Pokok Asam dan Basam Melalui Model Group Investigation (GI) - Aziz, Mukhtar Rahman (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The background of this classroom action research is that the attitude is less passionate, less active, the class is less student-centred, and sometimes there are those who play alone in the classroom which is a problem faced by SMP Negeri 9 Tangerang Selatan City, especially for physics subjects. Low student learning outcomes. The problem of this classroom action research is how students’ activities and learning outcomes of physics and student responses on the subject of Acids and Bases through learning models with Group Investigation in class VII-8 SMP Negeri 9 Tangerang Selatan City. And the purpose of this classroom action research is to describe student activities, determine student learning outcomes, and determine student responses to learning in class VII-8 SMP Negeri 9 Tangerang Selatan City. Through classroom action research (CAR) this problem is tried to be overcome by a learning model with the Group Investigation Method. CAR is done in 3 cycles. The research subjects were students of class VII-8 semester 1 of SMP Negeri 9 South Tangerang City, totaling 35 students. Data were obtained through observation, giving competency test tests, and distributing questionnaires. Then analyzed descriptively qualitatively. The results showed that students’ activities increased in groups, doing assignments, thinking together, and answering questions. Student learning outcomes increased and the response to the learning carried out was positive. Thus, from the implementation of classroom action research through a learning model with the group investigation method cycle I, Cycle II and Cycle III, it was concluded that it could improve physics learning outcomes on the subject of Acids and Bases at SMP Negeri 9 Tangerang Selatan City.